The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2165/11317090-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Menstrual Cycle on Exercise Metabolism

Abstract: The female hormones, oestrogen and progesterone, fluctuate predictably across the menstrual cycle in naturally cycling eumenorrhoeic women. Other than reproductive function, these hormones influence many other physiological systems, and their action during exercise may have implications for exercise performance. Although a number of studies have found exercise performance - and in particular, endurance performance - to vary between menstrual phases, there is an equal number of such studies reporting no differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
163
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(173 citation statements)
references
References 76 publications
2
163
1
7
Order By: Relevance
“…Conversely, it has been shown in previous studies, that exercise time to exhaustion is improved during the LP. This has been speculated that the role oestrogen plays on enhanced lipid metabolism, with spared glycogen and usually a supressed lactate response to exercise in the LP[32]. As seen in the present study, significant differences were found in lactate concentration between phases at 3 and 5 min post exercise.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Conversely, it has been shown in previous studies, that exercise time to exhaustion is improved during the LP. This has been speculated that the role oestrogen plays on enhanced lipid metabolism, with spared glycogen and usually a supressed lactate response to exercise in the LP[32]. As seen in the present study, significant differences were found in lactate concentration between phases at 3 and 5 min post exercise.…”
Section: Discussionsupporting
confidence: 72%
“…As seen in the present study, significant differences were found in lactate concentration between phases at 3 and 5 min post exercise. Therefore, there is the potential that the energy pathways may have been taxed differently between phase, for example it has been implicated previously that during the LP there is a lower contribution of anaerobic glycolysis and hence reduced La values[32]. A conclusive statement about this, however, is beyond the current scope of this study and perhaps requires deeper investigation with more sophisticated methodology (e. g. indirect calorimetry).…”
Section: Discussionmentioning
confidence: 88%
“…Estrogen could influence exercise metabolism28 and pharyngeal dilator muscle activity29. A significant increase in genioglossus electromyogram (EMGgg) was found in the postmenopausal group re-examined after hormone therapy2930.…”
Section: Discussionmentioning
confidence: 99%
“…Another sex hormone that might potentially alter substrate metabolism during exercise in women is progesterone. A complete examination of how progesterone and oestrogen interact in regulation of substrate metabolism during exercise is beyond the scope of this review, and the reader is directed to a review by Oosthuyse & Bosch () for more information. Briefly, progesterone is considered to act in an opposing manner to oestrogen; however, its role in influencing substrate utilization during exercise has not been fully established.…”
Section: Introductionmentioning
confidence: 99%